Factors contributing to the abandonment of heritage buildings in Malaysia / Nurul Aisyah Roslan and Mohd Azian Zaidi - Roslan, Nurul Aisyah; Zaidi, Mohd Azian (2023)
The findings of this research look at the causes of heritage building neglection. It provides a contributing cause to the lack of adoption of this technique in the Malaysian building sector. To discover the factor, a mixed method approach was utilized, literature review and a survey questionnaire (quantitative). In the phases of the literature review, several case studies were chosen to offer a thorough grasp of the issues involved in abandoned heritage buildings. For the questionnaire, nine (9) factors were identified through literature review tested with a survey questionnaire. The aspect identified in this research as a less appealing area, being remote from the city, depopulation, ineffective in scheduling, planning, and monitoring in maintenance work, documentation is being held in different places, heritage skills shortage, insufficient funds, high restoration cost as well as too costly to maintain was built from the construction of conceptual framework. The results from those eight (8) factors had mean values greater than 3.50, which only one factor resulting a value below 3.50.